Case report of myometrial window following fetoscopic treatment of twin‐twin transfusion syndrome: indications of underlying collagen vascular disease?. Issue 6 (9th May 2017) - Zaretsky, Michael V.; Manchester, David K.; Galan, Henry L.; Behrendt, Nicholas J.; Marwan, Ahmed I.; Liechty, Kenneth W.; Crombleholme, Timothy M.
Key Clinical Message: Intraperitoneal amniotic fluid leak is a known complication of fetoscopic procedures that usually resolves spontaneously with expectant management. Intraperitoneal amniotic fluid leak may persist after fetoscopic procedures due to a myometrial window as well as to persistent chorioamniotic membrane disruption, which may be amenable to surgical repair. Abstract : Intraperitoneal amniotic fluid leak is a known complication of fetoscopic procedures that usually resolves spontaneously with expectant management. Intraperitoneal amniotic fluid leak may persist after fetoscopic procedures due to a myometrial window as well as to persistent chorioamniotic membrane disruption, which may be amenable to surgical repair.